Development of an Islamic Value-Based Curriculum in Madrasah Aliyah - Adih Adih; Achmad Muzammil Alfan Nasrullah; Muhamad Sukri Situmeang; Orazguly Mammedov (STAI Publisistik Thawalib Jakarta, 2026)
The demands of globalization, which emphasize digital literacy and 21st-century skills, contrast with the implementation of Islamic value-based curricula, which are still largely traditional in madrasahs. This study aims to develop an Islamic value-based curriculum that is effective, adaptive, and responsive to the challenges of modern global education. This research employs a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study is supported by quantitative data collected through questionnaires and qualitative data obtained from in-depth interviews. The results show that the Islamic value-based curriculum developed at Madrasah Aliyah Darunna’im successfully integrates religious values, local pesantren values, and global competencies into a structured learning system. Validation results indicate a feasibility level of 88.75%, while the implementation stage shows that the curriculum effectiveness reaches 81.875% based on student and teacher responses. This curriculum includes religious subjects, general subjects, extracurricular activities, and co-curricular programs that complement each other in shaping students’ character. In addition, the curriculum improves Islamic understanding, discipline, communication skills, and readiness to face global challenges. However, several obstacles remain, particularly in facilities, teaching methods, and the consistency of program implementation in the madrasah. The conclusion of this study is that the Islamic value-based curriculum is effective, well-structured, and significantly improves students’ character and readiness to face global challenges. The significance of this research lies in the development of an innovative curriculum model with high validity and effectiveness that can be replicated in other Islamic educational institutions.